Semiconductor diode laser device adjuvanting intradermal vaccine. Issue 18 (25th April 2017) - Kimizuka, Yoshifumi; Callahan, John J.; Huang, Zilong; Morse, Kaitlyn; Katagiri, Wataru; Shigeta, Ayako; Bronson, Roderick; Takeuchi, Shu; Shimaoka, Yusuke; Chan, Megan P.K.; Zeng, Yang; Li, Binghao; et al.
Abstract: A brief exposure of skin to a low-power, non-tissue damaging laser light has been demonstrated to augment immune responses to intradermal vaccination. Both preclinical and clinical studies show that this approach is simple, effective, safe and well tolerated compared to standard chemical or biological adjuvants. Until now, these laser exposures have been performed using a diode-pumped solid-state laser (DPSSL) devices, which are expensive and require labor-intensive maintenance and special training. Development of an inexpensive, easy-to-use and small device would form an important step in translating this technology toward clinical application. Here we report that we have established a handheld, near-infrared (NIR) laser device using semiconductor diodes emitting either 1061, 1258, or 1301 nm light that costs less than 4000, and that this device replicates the adjuvant effect of a DPSSL system in a mouse model of influenza vaccination. Our results also indicate that a broader range of NIR laser wavelengths possess the ability to enhance vaccine immune responses, allowing engineering options for the device design. This small, low-cost device establishes the feasibility of using a laser adjuvant approach for mass-vaccination programs in a clinical setting, opens the door for broader testing of this technology with a variety of vaccines and forms the foundation for development of devices ready for use in the clinic.